Undergraduate Education in India : Dissecting the Perception Gaps in Students’ Expectations - Saji, T. G. (Prabandhan: Indian Journal of Management, 2020)
Providing quality curriculum and programmes within institutions is extremely important in shaping students’ perceptions of the overall quality of educational services. Hence, this research administered a survey among 198 final year students of affiliated Arts and Science colleges in Kerala, a state advanced in education and literacy in India, to collect their responses on expectations and satisfaction of the educational service performance at the institutional as well as the course levels. The gap analysis found that the students’ expectations were higher than their actual educational experiences in colleges, which was evident in all aspects of the services under investigation. The highest gaps for the institutions were in placement support, timely conduct of examination, and adequate infrastructure ; while for the courses, it was in skill development and employability. However, the results of the regression analysis revealed that not all the factors claimed by the students in gap analysis appeared as the significant determinants of the overall satisfaction towards higher education services generally in India, particularly in Kerala.